LESSONS FROM TALLAHALA: WHAT HAVE WE LEARNED FOR TURKEY MANAGEMENT INTO THE 21st CENTURY? - Darren A. Miller; Michael J. Chamberlain; Bruce D. Leopold; George A. Hurst (Wildlife Society Bulletin)
Abstract: Ecological studies of the eastern wild turkey (Meleagris gallopavo silvestris) were conducted on the Tallahala Wildlife Management Area (Tallahala), Mississippi, during 1983–97. We used data from this project to discuss possible reasons for an observed population decline, make habitat management recommendations for southern forested environments, and discuss design, implementation, and importance of conducting long‐term research. Although predation was important to turkey ecology on Tallahala, the population decline was a result of poor reproduction due to low rates of nest initiation, nonexistent nesting by juvenile females, and lack of renest success. Habitat quality on Tallahala was likely low due to lack of fields and open areas, and may have caused turkeys to be in poor condition, possibly manifested in the observed low reproductive rates. However, the population decline may have recently reversed possibly due to several years of good reproduction. Long‐term research enabled us to examine trends in population parameters, adjust objectives as new data were gathered, examine many aspects of turkey ecology over time, and collect data over periods of environmental vagaries. For successful implementation of long‐term research, we recommend attention to consistent collection of baseline data, standardization of data collection, quarterly reviews and annual updates of all databases, and development of multiple objectives. Habitat management in southern forested environments should maintain stand diversity across the landscape, and include frequent disturbance of mature pine to maintain herbaceous groundstory conditions, a preponderance of mature forest stands, and conservation of bottomland hardwood stands. Long‐term, multidimensional studies are crucial to advancement of our knowledge of wild turkey ecology.